La Nueva Oligarquía Latinoamericana Ideología y Democracia - Saxe Fernández, Eduardo E. (Editorial Universidad Nacional de Colombia (UNAL), 1999)
In this controversial essay, Eduardo Saxe Fernández argues that the return of liberalism to Latin America is accompanied by the return of oligarchic governments. The new Latin American oligarchies are based on a purely formalist democracy, while old and new methods of social and political exclusion continue to be practiced, the regressive redistribution of wealth that has characterized the region since the Second World War has worsened starting from the 80's, facilitating the emergence of those powerful oligarchic groups in which political power is combined, as in classical models, with financial power.